Konsep Integrasi Islam Dan Sains : Peluang Dan Tantangan Bagi Universitas Islam Negeri Sunan Kalijaga - Lubis, Abdul Hadi; Helmiati, Helmiati; Nazir, M (Jurnal Penelitian Ilmu Pendidikan Indonesia, 2025)
The purpose of this study is to explore the concept of the integration of Islam and science: opportunities and challenges for Sunan Kalijaga State Islamic University (UIN). This research employs a qualitative method. The findings indicate that the opportunities for integrating Islam and science include the development of a new scientific paradigm, enhancing the relevance of Islamic education in line with contemporary developments, and supporting UIN Sunan Kalijaga's efforts to become a World-Class University in Islamic Studies. However, the challenges faced include epistemological differences between religious knowledge and science, the readiness of human resources, appropriate curriculum development, and academic resistance to the concept of integration. As a solution, UIN Sunan Kalijaga has taken several strategic steps, such as organizing academic conferences, opening new study programs, and designing an integration-based curriculum. Through these efforts, the integration of Islam and science is expected to continue evolving and contribute to Islamic education and the advancement of civilization.